Prevalnce of Helicobacter Pylori in Perforated Peptic ulcer - Aman, Zahid; Afridi, Viqar; Khan, Jehangir (Journal of Postgraduate Medical Institute, 2011)
Most patients with chronic peptic ulcer disease have helicobacter pylori (H. Pylori) infection. But there are very few reports regarding the prevalnce of H. Pylori infection in peptic ulcer perforations, which is the commonest complication of peptic ulcer disease. teh aim of this study was to draw this association. 94 consecutive patients suffering from acute peptic ulcer perforation were included in this prospective clinical study. Per-operative biopsies were taken from the ulcer margins and antral mucosa for H. Pylori. the criteria for H. Pylori positive wa a positive rapid urease test for eivdence of H. Pylori infection on histological examination using Giemsa and H&E stains. Among these 94 patients 85.1% (80 = n) were positive for H. Pylori, which is well above the usual prevalnce of 45% in normal population. H Pylori infection was significantly more common in cases of chronic dyspepsia (>6 months), but not significantly related to sex, blood group, addiction and family history of peptic ulcer disease. There is a very high prevalnce of H. Pylori infection in patients with perforated peptic ulcer, than in those without it. an early and appropriate H Pylori eradication therapy will reduce the relapse rate after simple closure and the need for a definitive acid reduction surgery later on.